Inter and intra-rater reliability of the scoring and analysis of Bender Gestalt and Human Figure Drawing protocols in a clinical setting - Suttner, Vivien (My University, 2014)
The Bender Gestalt and the analysis of the Human Figure Drawing are amongst the most widely used assessment tools in South Africa. This research examines the inter and intrarater reliability of scores and diagnoses made by two clinicians from a clinical sample of 104 Bender Gestalt and Human Figure Drawing protocols. Two scoring sessions were held, with a three week interval between them. The protocols were scored according to the Koppitz criteria. On the basis of these results the clinicians placed each child into one of four proscribed diagnostic categories: Exhibiting visual-perceptual difficulties; emotional difficulties; both difficulties; neither difficulties. The results indicated significant inter-rater differences between the raters’ diagnoses, and scoring of the Bender Gestalt. With regards to intra-rater differences, is. individual differences from session one to two, significant differences were evident in the scoring of the Bender Gestalt. No significant intra-rater differences emerged on the scoring of the Human Figure Drawing. These results indicate that there is cause for concern regarding the reliability of clinicians’ interpretations based on The Bender Gestalt and Human Figure Drawings.